Pulmonary Hypertension and the Gut Microbiome - Thomas Mason; Bhashkar Mukherjee; Philip Marino (Biomedicines, 2024)
The gut microbiome and its associated metabolites are integral to the maintenance of gut integrity and function. There is increasing evidence that its alteration, referred to as dysbiosis, is involved in the development of a systemic conditions such as cardiovascular disease (e.g., systemic hypertension, atherosclerosis). Pulmonary hypertension (PH) is a condition characterised by progressive remodelling and vasoconstriction of the pulmonary circulation, ultimately leading to right ventricular failure and premature mortality if untreated. Initial studies have suggested a possible association between dysbiosis of the microbiome and the development of PH. The aim of this article is to review the current experimental and clinical data with respect to the potential interaction between the gut microbiome and the pathophysiology of pulmonary hypertension. It will also highlight possible new therapeutic targets that may provide future therapies.